2013
DOI: 10.4155/fmc.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Protection of MLC 1 Against Cardiac Ischemia/Reperfusion-Induced Degradation: A Novel Therapeutic Concept for the Future

Abstract: Cardiovascular diseases are a major burden to society and a leading cause of morbidity and mortality in the developed world. Despite clinical and scientific advances in understanding the molecular mechanisms and treatment of heart injury, novel therapeutic strategies are needed to prevent morbidity and mortality due to cardiac events. Growing evidence reported over the last decade has focused on the intracellular targets for proteolytic degradation by MMP-2. Of particular interest is the establishment of MMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…A classic example of combination therapy for heart diseases is the therapeutic strategy that includes diuretics, β-blockers, ACE inhibitor, calcium channel blockers and other agents (34). Recent studies have demonstrated a synergistic protection against I/R-induced injury via several mechanisms contributing the contractile protein degradation (35). In the current study, both Angpt2 siRNA and FGF21 were found to exert a cardioprotective effect, since overexpression of Angpt2 is harmful to the cardiovascular system and endocrine FGF21 has beneficial effects in heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…A classic example of combination therapy for heart diseases is the therapeutic strategy that includes diuretics, β-blockers, ACE inhibitor, calcium channel blockers and other agents (34). Recent studies have demonstrated a synergistic protection against I/R-induced injury via several mechanisms contributing the contractile protein degradation (35). In the current study, both Angpt2 siRNA and FGF21 were found to exert a cardioprotective effect, since overexpression of Angpt2 is harmful to the cardiovascular system and endocrine FGF21 has beneficial effects in heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin molecule consists of two heavy chains, myosin heavy chain α (MHC-α) and myosin heavy chain β (MHC-β), and two pairs of light chains: regulatory (RLC/MLC2) and essential (ELC/MLC1), divided into atrial (ALC1) and ventricular (VLC1) [13,17,31,[34][35][36]. Since MHC have actin and ATP binding sites and present the molecular motor of muscle contraction [26][27][28]30,32], ELCs (MLCs1) are primarily responsible for maintaining MHC conformation and regulating contraction strength and speed [1,21,37,38]. In the current research, we showed that VLCs1 were degraded and released into extracellular space due to I/R-induced oxidative stress, as evidenced by the decreased heart level of VLC1 and its release into coronary effluents.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of blood flow to pre-ischemic myocardium leads to ischemia-reperfusion injury (IRI), which subsequently results in deterioration of cardiac function [1][2][3][4][5][6]. Numerous clinical manifestations of IRI including myocardial necrosis, arrhythmia, and endothelial and microvascular dysfunction are observed [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies presented in this review show that testing potential therapeutic agents for synergism in reperfusion protection should lead to the development of a “drug cocktail” or a “super pill” to protect the hearts of human patients from I/R injury. The concept of protecting I/R hearts using the synergistic action of drugs inhibiting modifications of contractile proteins together with inhibition of MMP-2 activity is currently under investigation in my lab and has been reviewed [158, 159]. …”
Section: Final Remarks and Possible Clinical Implicationsmentioning
confidence: 99%